Annamária-Izabella Pazsint, "Private Association in the Pontic Greek Cities (6th century BC-3rd century AD)", Peeters, Leuven - Paris - Bristol CT, 2022, 387 p. - TODOR, Paula (Studia Universitatis Babeș-Bolyai Historia, 2025)
The present work is based on the doctoral thesis of the author Annamária-Izabella Pazsint, translated and revised after the defence which took place in 2019, and represents a comprehensive study on the phenomenon of private associations in the Pontic cities from the 6th century BC to the 3rd century AD. It is a social history and prosopographic study, providing essential information on the development of associations from their emergence in this geographic area until their decline in the 3rd century AD. A. I. Pazsint employs a multidisciplinary approach, using archaeological, epigraphic, and literary evidence to conduct network analyses of interconnected members from various associations. The work, comprising 387 pages, is structured into six chapters, along with an introduction, conclusions, glossary of terms, appendices, figures, and illustrations. The appendices contain two extensive catalogues: one listing all epigraphic sources used in the study, and another listing all association members present in the inscriptions, 1983 individuals in total. The figures and illustrations include a thematic map, a table showing the geographical distribution of terminology, statistical graphs on the geographical distribution of inscriptions and associations, the chronological distribution of inscriptions, their types based on the city, and the types of materials used.